$Id:$ /* -------------------------------------------------------------------------- CppAD: C++ Algorithmic Differentiation: Copyright (C) 2003-14 Bradley M. Bell CppAD is distributed under multiple licenses. This distribution is under the terms of the Eclipse Public License Version 1.0. A copy of this license is included in the COPYING file of this distribution. Please visit http://www.coin-or.org/CppAD/ for information on other licenses. -------------------------------------------------------------------------- */ $begin erf_forward$$ $spell erf Taylor $$ $index erf, forward theory$$ $index theory, erf forward$$ $index forward, erf theory$$ $section Error Function Forward Taylor Polynomial Theory$$ $head Derivatives$$ Given $latex X(t)$$, we define the function $latex \[ Z(t) = \R{erf}[ X(t) ] \]$$ It follows that $latex \[ \begin{array}{rcl} \R{erf}^{(1)} ( u ) & = & ( 2 / \sqrt{\pi} ) \exp \left( - u^2 \right) \\ Z^{(1)} (t) & = & \R{erf}^{(1)} [ X(t) ] X^{(1)} (t) = Y(t) X^{(1)} (t) \end{array} \] $$ where we define the function $latex \[ Y(t) = \frac{2}{ \sqrt{\pi} } \exp \left[ - X(t)^2 \right] \] $$ $head Taylor Coefficients Recursion$$ Suppose that we are given the Taylor coefficients up to order $latex j$$ for the function $latex X(t)$$ and $latex Y(t)$$. We need a formula that computes the coefficient of order $latex j$$ for $latex Z(t)$$. Using the equation above for $latex Z^{(1)} (t)$$, we have $latex \[ \begin{array}{rcl} \sum_{k=1}^j k z^{(k)} t^{k-1} & = & \left[ \sum_{k=0}^j y^{(k)} t^k \right] \left[ \sum_{k=1}^j k x^{(k)} t^{k-1} \right] + o( t^{j-1} ) \end{array} \] $$ Setting the coefficients of $latex t^{j-1}$$ equal, we have $latex \[ \begin{array}{rcl} j z^{(j)} = \sum_{k=1}^j k x^{(k)} y^{(j-k)} \\ z^{(j)} = \frac{1}{j} \sum_{k=1}^j k x^{(k)} y^{(j-k)} \end{array} \] $$ $end